Detection Of Human Face Targets with Viola-Jones Method - Rahmiati; Ambiyar; Rika Melyanti; Eka Sabna (JAIA - Journal of Artificial Intelligence and Applications, 2021)
This study aims to implement Viola Jones into a simple face detection system by utilizing the existing library in Open CV and using the Python programming language. In this study, there were 10 sample images consisting of 8 images of human faces and 2 images of animals. The results of the study were 9 images were successfully detected and 1 image was less precise in determining the face. The system can detect the presence of several (more than one) faces in an image. The system can also detect an object that resembles a face when the object has the same contour as a human face, for example, a face on a statue.